2021
DOI: 10.1002/aenm.202101650
|View full text |Cite
|
Sign up to set email alerts
|

Hard Carbon Anodes for Next‐Generation Li‐Ion Batteries: Review and Perspective

Abstract: Carbonaceous materials have been accepted as a promising family of anode materials for lithium‐ion batteries (LIBs) owing to optimal overall performance. Among various emerging carbonaceous anode materials, hard carbons have recently gained significant attention for high‐energy LIBs. The most attractive features of hard carbons are the enriched microcrystalline structure, which not only benefits the uptake of more Li+ ions but also facilitates the Li+ ions intercalation and deintercalation. However, the boomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
158
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(177 citation statements)
references
References 208 publications
(269 reference statements)
2
158
0
Order By: Relevance
“…[25] Therefore, Yoshida et al used Li-Naph/tetrahydrofuran (THF) solution to reduce the silicon anode. [26] The studies of voltage and 7 Li nuclear magnetic resonance showed that amorphous Si experiences alloying reaction to form Li x Si, and the degree of lithiation will be affected by the concentration of solution. The Si anode can be replenished a capacity of 1200 mAh g À 1 by 0.1 M Li-Naph solution within 1 h, and its cycling performance is unaffected compared to the untreated Si anode.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Therefore, Yoshida et al used Li-Naph/tetrahydrofuran (THF) solution to reduce the silicon anode. [26] The studies of voltage and 7 Li nuclear magnetic resonance showed that amorphous Si experiences alloying reaction to form Li x Si, and the degree of lithiation will be affected by the concentration of solution. The Si anode can be replenished a capacity of 1200 mAh g À 1 by 0.1 M Li-Naph solution within 1 h, and its cycling performance is unaffected compared to the untreated Si anode.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…The disordered orientation of graphene layers in HC provides enlarged surface area to store more lithium (400-1000 mAh g À 1 ), it also leads to severer side reactions, resulting in a 20-40 % lithium loss in initial cycle. [7] The silicon anode with ultra-high theoretical capacity (Li 15 Si 4 = 3579 mAh g À 1 ) [8] is limited by the low ICE and subsequent rapid capacity decay, mainly owing to the 300 % volume expansion and less stable SEI during lithiation. [9] While, the oxide anodes are also facing the same challenge of lower ICEs during lithiation/delithiation.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by graphite's inability to store sodium ions and the energy transition to a sustainable economy, many groups have focused their research on developing of green, cheap and efficient carbon electrodes for next-generation rechargeable metal-ion batteries. Hard (i.e., non-graphitizable) carbons have attracted special attention as negative electrodes due to their high ability to store more lithium ions than graphite and their suitability for NIBs (Soltani et al, 2021;Xie et al, 2021). Hard carbons are usually obtained from the pyrolysis of biomass waste, sugars, or phenolic resins.…”
Section: Rechargeable Batteriesmentioning
confidence: 99%
“…Recently, research on carbon materials and graphene as anode materials for lithiumion batteries has been conducted [2][3][4]. There are several types of carbon allotropes [5,6], including graphene, graphite, diamond, carbon nanowalls (CNW), carbon nanotubes (CNT), and fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…There are several types of carbon allotropes [5,6], including graphene, graphite, diamond, carbon nanowalls (CNW), carbon nanotubes (CNT), and fullerenes. Graphene has a flat 2D structure in which carbon atoms form sp 2 bonds in a hexagonal shape, while graphite is a structure in which graphene forms multiple layers by π-π bonds [7,8]. In CNW, graphene grows vertically to form a nanowall structure and carbon nanotubes are bonded by rolling graphene into a cylindrical shape.…”
Section: Introductionmentioning
confidence: 99%